Solving multi-objective aeroassisted spacecraft trajectory optimization problems using extended NSGA-II - Chai, Runqi; Savvaris, Al; Tsourdos, Antonios; Chai, Senchun (AIAA, 2017)
This paper focuses on the application of an extended NSGA-II algorithm to the aero-assisted spacecraft trajectory optimization problems. A new multi-objective spacecraft optimal control model is formulated and parameterized using discretization method. The resulting multi-objective nonlinear programming problem is then solved via the multi-objective evolutionary solver. In order to deal with path constraints that naturally arise in practical trajectory planning problems, the original NSGA-II approach is extended by introducing a new constraint handling strategy. Simulation results are provided to illustrate the effectiveness and feasibility of the enhanced NSGA-II algorithm in dealing with spacecraft trajectory optimization problems.